A novel method to correctly place the fasciotomy incision for decompression of the anterior and peroneal compartments of the leg. Issue 4 (April 2016) - Pallister, Ian; Morris, Rhys M.; Lloyd, Tom; Marsden, Nicholas J.; Wright, Thomas; Gilbert, Michael; Phillips, Jonathan
Abstract: Incorrectly placed fasciotomy incisions can lead to catastrophic complications in compartment syndrome. Two distinctly different techniques are widely practiced to decompress the anterior and peroneal compartments. In one technique the anterior compartment is decompressed directly, and then the peroneal via the inter-muscular septum, avoiding the peroneal perforators. The second technique relies on surface anatomy landmarks to place the skin incision immediately over the inter-muscular septum, and then the respective fascial envelopes are incised separately. A study in healthy active volunteers was conducted to explore the feasibility of a new technique for the placing the incision very accurately over the inter-muscular septum and so avoiding perforator vessels. Hypothesis The inter-muscular septum can be reliably identified using hand-held ultrasound, and confirmed with MRI. Methods: Fourteen healthy active volunteers underwent hand-held ultrasound to identify the antero-lateral inter-muscular septum in the left lower limb, which was then marked using cod liver oil capsules. The positions of the anterior, septal and peroneal perforators were then identified using hand-held Doppler, and marked in the same way. MRI was then used to measure the relationship between the surface land marks, the septum (compared to its US position), and the relationship of the perforators themselves. Results: Hand held ultrasound was successful in identifying the position of the inter-muscular septum in healthy volunteers, as confirmed on MRI scanning. The position and number of peroneal and anterior perforators proved very variable. Direct decompression of the anterior compartment would result in the loss of all anterior perforators in all subjects. Decompression with the skin incision over the inter-muscular septum would not jeopardise any peroneal muscular perforators. Conclusion: This new technique enables decompression both the anterior and peroneal compartments through an accurately placed incision, sparing the greatest number of perforators. Two brief case histories in which the technique was used are presented.